Integrins on neutrophils are dispensable for migration into three-dimensional fibrin gels - Koenderman, Leo; van der Linden, Jan A. M.; Honing, Henk; Ulfman, Laurien H. (Thrombosis and Haemostasis, 2010)
The innate immune system and the blood haemostasis system function cooperatively in many pathological conditions such as acute respiratory distress syndrome, deep venous thrombosis, ischaemia/reperfusion injury and cardiovascular disease. Infiltration of neutrophils into thrombotic substrates such as fibrin clots supports fibrinolysis, tissue damage and inflammation. Despite the importance of integrins in neutrophil attachment to fibrin-coated surfaces under flow conditions, little is known about their role in migration processes in shear free two-dimensional (2D) and three-dimensional (3D) fibrin(ogen) environments. Therefore, the present study was designed to study the role of functional integrins in mediating neutrophil migration on and in fibrin matrices. Time lapse video sequences of neutrophil chemokinesis and chemotaxis were made under conditions of active- or non-active integrins. Interestingly, migration of neutrophils on 2D fibrinogen coated surfaces and 3D fibrin matrices is independent of integrins as the response is not sensitive to αM-(CD11b) and β2-(CD18) blocking antibodies and/or chelation of Ca2+ and Mg2+ by EDTA in bivalent ion-free buffers. The blocking integrin antibodies were shown to be functionally active in regular adhesion assays. Our study shows that integrins are dispensable for migration on 2D and in 3D fibrin matrices, both when neutrophils enter into the fibrin matrix and when captured in the matrix.
Keywords: Migration; 3D matrix; fibrin; neutrophils; integrins; chemotaxis